Building the Concept of Siri'na Pacce in The Aspiration of Corporate Social Responsibility - Ari Utomo Saputra; Nengsi Sudirman; Ari Ayu (www.amertainstitute.com, 2024)
Purpose: This study aims to explore the application of the cultural value of